Assessment of nocturnal hypertension by ambulatory blood pressure monitoring at the forearm in people with morbid obesity. Issue 9 (13th August 2020) - Pucci, Giacomo; D'Abbondanza, Marco; Camilli, Matteo; Bisogni, Valeria; Anastasio, Fabio; Gandolfo, Vito; Alcidi, Riccardo; Mojovic, Natasa; Ministrini, Stefano; Lupattelli, Graziana; Vaudo, Gaetano
Abstract: Blood pressure (BP) measurement at the forearm (FA) has been proposed as alternative site to upper arm (UA) in people with morbid obesity (MO). We compared nocturnal BP readings simultaneously taken at FA and UA by ambulatory blood pressure monitoring (ABPM). Fourteen individuals with MO and seven normal‐weight controls underwent nocturnal ABPM with two devices placed at the UA and contralateral FA, respectively. Agreement between FA‐UA BP, diagnosis of nocturnal hypertension, and potential determinants of BP differences were evaluated. BP at the FA was significantly higher than UA in both people with MO and controls. FA‐UA differences in systolic and diastolic BP were similar in people with MO and controls. Nocturnal hypertension was diagnosed in 10 subjects (48%) according to UA BP and in 13 subjects (62%) according to FA BP (concordance 76%, moderate agreement). ΔFA‐UA systolic BP was associated with ratio between FA/UA circumferences ( R  = 0.45, P  < .05) and with cuff‐UA slant angle difference ( R  = 0.44, P  < .05). In conclusions, in people with MO, the agreement between FA and UA nighttime BP measured by ABPM is sub‐optimal. Our results raise uncertainty in using ABPM at the FA as an alternative to UA placement in people with MO for the diagnosis of nocturnal hypertension.